Mobile technology for health care in rural China - Zhao Ni; Bei Wu; Catherine Samples; Ryan J. Shaw (Elsevier, 2014)
With the proliferation of mobile technologies in China, the Chinese mobile medical applications market is growing rapidly. This may be particularly useful for Chinese rural populations who have limited access to quality medical care where mobile technologies can reach across geographic and socioeconomic boundaries and potentially increase access to care and improve health outcomes.